Plan para la creación de una empresa dedicada al cultivo hidropónico de tomate en invernadero. - Alfaro-González, Laura; Morales-García, Tiky (Instituto Tecnológico de Costa Rica, 2011)
A more sustainable production system such as hydroponics in a protected environment is an attractive alternative to expand production, improve product quality and facilitate compliance with the provisions or requirements of the market, so it is a good choice for growing tomato, one of the most consumed vegetables worldwide. The decision to enter this area is to take this business opportunity, as an added value using Professional Project Management and thus, maximize the economic benefits that a currently unused property can provide. The present investigation is to provide an implementation plan to facilitate the creation of a company dedicated to growing hydroponic tomatoes. For this purpose, we developed an exploratory-descriptive, which identified key data about the project and the relevant variables to the market opportunity as well as current industry position that eventually belong to the company and the particular technical requirements of the activity commercial use. To clearly define the work required for completing the project successfully, defined requirements, processes and tasks to be performed based on the needs of different stakeholders, as well as compliance binding to it. In addition, it created all the tools that allow the process to be carried out in an orderly manner and under a single language proposal for implementation. The initial investment required for the project is 355.720.195,35 colones and its implementation is estimated at 409 days, or 19 months.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2011.
Keywords: Gestión de calidad; Gestión de riesgos; Información; Publicidad; Impacto ambiental; Desechos sólidos